2017
DOI: 10.1016/j.jadohealth.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette Use, Cigarette Smoking, Dual Use, and Problem Behaviors Among U.S. Adolescents: Results From a National Survey

Abstract: Purpose There is a need to obtain greater clarity regarding adolescents’ e-cigarette use and their use with a wider range of risk behaviors. This study examines the associations among past-month e-cigarette use only, traditional cigarette smoking only, dual use (i.e., concurrent e-cigarette use and cigarette smoking), school-related (i.e., truancy and poor academic performance), and substance-related (i.e., alcohol use, binge drinking, marijuana use, illicit drug use, and nonmedical prescription drug use) risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
88
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(101 citation statements)
references
References 37 publications
11
88
1
1
Order By: Relevance
“…Previous studies have shown that e‐cigarette users tend to have higher rates of conventional cigarette use, and our work supports this assertion on a national level. McQueen et al specifically examined 110 patients with head and neck cancer and a smoking history and demonstrated that non–e‐cigarette users achieved higher quit rates than e‐cigarette users.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies have shown that e‐cigarette users tend to have higher rates of conventional cigarette use, and our work supports this assertion on a national level. McQueen et al specifically examined 110 patients with head and neck cancer and a smoking history and demonstrated that non–e‐cigarette users achieved higher quit rates than e‐cigarette users.…”
Section: Discussionsupporting
confidence: 89%
“…8 Recently, in adolescents and youths, e-cigarette use was also shown to be associated with conventional cigarette and alcohol use. 7 In older adults, who tend to use ecigarettes as smoking cessation aids, 9 e-cigarette use has been demonstrated to be significantly associated with tobacco cigarette use [10][11][12][13][14][15] ; longitudinal studies suggest that e-cigarettes are not effective for smoking cessation. 9,10 However, the relationship between e-cigarettes and alcohol use in adults is less clearly documented, with studies finding mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of studies on the dual use of illicit drugs and e-cigarettes in Canada, it is not possible to compare these results to previous Canadian data to assess trends. However, some international studies have shown findings similar to those in the present study [15][16][17]34]. Additionally, even fewer studies have explored the potential use of ecigarettes as illicit drug delivery systems.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, e-cigarettes have been associated with a decline in overall health, including lung tissue damage, worse cardiovascular health outcomes and increased inflammatory responses [10][11][12]. Although none in Canada, some international studies have also shown positive associations between risky behaviors such as the use of illicit drugs, marijuana, alcohol and e-cigarette use [13][14][15][16][17][18][19][20][21][22]. Consequently, increased concerns have arisen among substance use researchers since recent e-cigarette designs have grown to accommodate illicit substances.…”
Section: Introductionmentioning
confidence: 99%
“…Participants with high perceived risk could be concerned about the possibility of increased nicotine dependence or other risks associated with dual-use. 22,23 In addition, compared to those with low-risk perception, those with high-risk perception had higher odds of e-cigarette-only use relative to cigarette-only users. Our findings indicate that, relative to e-cigarette users, those with a high-risk perception of both products had lower odds of dual-use than those with a low-risk perception of both products.…”
Section: Discussionmentioning
confidence: 99%